Muslim Teachers’ Characteristics Based on Integrated Holistic Education System - Sabilan, Sapie; Hamzah, Mohd Isa; Tamuri , Ab. Halim; Lip, Suhana Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to explore Muslim teachers’ characteristics based on Integrated Holistic Education System (IHES), which is applied in the education system under Selangor State Religious Department (JAIS). IHES under JAIS education system aims to give thorough education, nurture good akhlaq among students and produce Al Quran generation equipped with knowledge and taqwa. The exploration of Muslim teachers’ characteristics and roles is based on studies related to the evaluation on JAIS IHES education process from the aspects of ta’lim, ta’dib, tadrib, taujih and irsyad. In this research, a total of 122 JAIS Islamic education teachers from Hulu Langat and Sepang districts were selected as respondents for the pilot study. The reliability and validity of the instrument used had been tested by using Item Content Validity Index (I-CVI), which involved ten experts. I-CVI was used to determine the level of reliability among the selected experts. The result of the average score of Item Content Validity Index (S-CVI) showed a high value for the construct of IHES education process with 0.941. While the value of Cronbach Alpha showed a high value of consistency with the value of 0.92 and can be considered as in acceptable range. Based on I-CVI and Cronbach Alpha evaluation, it can be concluded that the items constructed can be accepted as representation of sub construct for IHES education process namely ta’lim, ta’dib, tadrib, taujih and irsyad. The findings from the research also explained on the roles of SRA JAIS teachers as mu‘allim, muaddib, mudarrib, muwajjih dan mursyid..